2015
DOI: 10.1371/journal.pone.0126093
|View full text |Cite
|
Sign up to set email alerts
|

Where Do Ethno-Linguistic Groups Meet? How Copresence during Free-Time Is Related to Copresence at Home and at Work

Abstract: This paper analyzes ethnic segregation across the whole activity space—at place of residence, place of work, and during free-time. We focus on interethnic meeting potential during free-time, measured as copresence, and its relationship to copresence at place of residence and work. The study is based on cellphone data for a medium-sized linguistically divided European city (Tallinn, Estonia), where the Estonian majority and mainly Russian-speaking minority populations are of roughly equal size. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 53 publications
2
29
0
6
Order By: Relevance
“…We also found that residential dissimilarity was strongly correlated with activity space dissimilarity with a correlation coefficient of r=79.96 (n=970, p< .01) at the district level and r=83.83 (n=81, p< .01) at the province level. In line with previous literature, we found that activity space dissimilarity was more often less than residential dissimilarity [22].…”
Section: Resultssupporting
confidence: 92%
“…We also found that residential dissimilarity was strongly correlated with activity space dissimilarity with a correlation coefficient of r=79.96 (n=970, p< .01) at the district level and r=83.83 (n=81, p< .01) at the province level. In line with previous literature, we found that activity space dissimilarity was more often less than residential dissimilarity [22].…”
Section: Resultssupporting
confidence: 92%
“…Residential segregation is higher than that in other domains of daily life (Toomet et al 2015). The Russian-speaking minority dominates panel housing districts (Kährik and Tammaru 2010), whereas Estonians prefer detached housing (Kährik 2002).…”
Section: Ethnic Groups and Segregation In Estoniamentioning
confidence: 90%
“…Few authors have studied segregation in activity locations in Estonia. Toomet et al (2015) found that compared with workplaces and residences, leisuretime locations for Estonians and Russian speakers in Tallinn are less segregated. Silm and Ahas (2014b) indicate that Estonians' and Russian speakers' activity spaces outside Tallinn are, however, segregated and the latter tend to visit districts which are mostly populated by the Russian-speaking minority.…”
Section: Ethnic Groups and Segregation In Estoniamentioning
confidence: 95%
See 1 more Smart Citation
“…In terms of scale, the most extensive empirical studies have been the ones addressing the segregation between the Estonian majority and the Russian-speaking minority in Estonia, employing data from mobile phones to study the degree of co-presence between the two groups in urban spaces (Järv et al 2015;Silm & Ahas 2014;Toomet et al 2015). The findings indicated that daily mobility decreases residential segregation depicted in census records based on place of residence, although there is considerable variation between different time frames as well as between different types of residential areas.…”
Section: Segregation Across Multiple Spatial Domainsmentioning
confidence: 99%